(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
In recent years, play and warfare have been the focus of many research programs. The book here reviewed gathers papers presented at a conference held in Elche in 2021 and examines for the first time the relationship between warfare and play in Antiquity. Adopting different methodologies and hermeneutic perspectives, the studies collected explore the topic and underline its complexity.